Vertical Guided Bone Regeneration in the Rabbit Calvarium Using Porous Nanohydroxyapatite Block Grafts Coated with rhVEGF165 and Cortical Perforation - Liu W; Du B; Tan S; Wang Q; Li Y; Zhou L (International Journal of Nanomedicine, 2020)
Weizhen Liu,1,* Bing Du,2,* Siyi Tan,3 Qin Wang,4 Yi Li,1 Lei Zhou5 1Department of Periodontics, School of Stomatology, Southern Medical University, Guangzhou, Guangdong, People’s Republic of China; 2Center of Stomatology, The Second People’s Hospital of Foshan, Foshan, Guangdong, People’s Republic of China; 3Center of Stomatology, Panyu Central Hospital, Guangzhou, Guangdong, People’s Republic of China; 4Department of Oral Maxillofacial Surgery, School of Stomatology, Southern Medical University, Guangzhou, Guangdong, People’s Republic of China; 5Center of Oral Implantology, School of Stomatology, Southern Medical University, Guangzhou, Guangdong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lei ZhouCenter of Oral Implantology, School of Stomatology, Southern Medical University, Guangzhou, Guangdong 510280, People’s Republic of ChinaTel +86 20 8423 3801Fax +86 20 8443 3177Email zho668@263.netIntroduction: Vertical bone augmentation without osseous walls to support the stability of clots and bone grafts remains a challenge in dental implantology. The objectives of this study were to confirm that cortical perforation of the recipient bed is necessary and to evaluate whether nanohydroxyapatite (nHA) block grafts coated with recombinant human vascular endothelial growth factor165 (rhVEGF165) and cortical perforation can improve vertical bone regeneration.Materials and Methods: We prepared nHA blocks coated with or without rhVEGF165 on the rabbit calvarium through cortical perforation, and designated the animals as the nonperforated group (N-nHA), rhVEGF165 group (NV-nHA), perforated group (P-nHA) and rhVEGF165 on perforated group (PV-nHA). Micro-computed tomography (micro-CT) and fluorescence microscopy were selected to evaluate parameters of vertical bone regeneration at 4 and 6 weeks.Results: The ratio of the newly formed bone volume to the titanium dome volume (BV/TV) and the bone mineral density (BMD) were significantly higher in the PV-nHA group than in the N-nHA group at 4 and 6 weeks, as determined using micro-CT. The fluorescence analysis showed slightly greater increases in new bone regeneration (NB%) and vertical height (VH%) gains in the P-nHA group than in the N-nHA group. Greater increases in NB% and VH% were observed in groups treated with rhVEGF165 and perforation than in the blank groups, with significant differences detected at 4 and 6 weeks (N-nHA compared with PV-nHA, p< 0.05). A greater VH% that was observed at the midline of the block in the PV-nHA group than in the other three groups at both time points (0.75± 0.53% at 4 weeks and 0.83± 0.42% at 6 weeks).Conclusion: According to the present study, cortical perforation is necessary and nHA blocks coated with rhVEGF165 and decoration could work synergistically to improve vertical bone regeneration by directly affecting primary osteoblasts and promoting angiogenesis and osteoinduction.Keywords: cortical perforation, vertical bone regeneration, hydroxyapatite blocks, fluorescence, angiogenesis